Humanising higher education through a culturally responsive curriculum - Maluleka, K.J. (South African Journal of Higher Education, 2020)
During the student protests in South Africa, students indicated that they were still taught irrelevant knowledge after 25 years of independence. The decolonisation of the curriculum was one of the demands of the Fees-Must-Fall protests. The purpose of this chapter is to join the debate by determining the way in which the higher education curriculum can be humanised by making it culturally responsive. This was a qualitative study and the sample included six academics selected from the programme of the London International Conference on Education (LICE‐2018) and World Congress on Special Needs Education held from 10 to 13 December 2018 at Cambridge, UK. Presenters whose papers were related to the contextualisation of the curriculum were targeted. An e-mail requesting a 60-minute interview was sent to ten of them. Only five agreed to participate. The participants cited initiatives by Tanzanians (Ujamaa) and Zimbabweans (unhu) to promote culturally responsive education. This study makes recommendations that include education that encourages self-reliance.